Guides on Establishment and Management of Privately Owned Counselling Centres - Yahaya, Lasiele Alabi; Muhammed, Shuaib A.; Hammed, Olawale A. (International Journal of Educational Management, 2021)
Guidance and counselling is an essential educational programme which focuses onhuman development. In view of its importance, this paper provides guides on establishment and management of privately owned counselling centres. It highlights the concepts of guidance and counselling, factors to be considered in establishing private guidance and counselling centres and the facilities required. The paper also dwells on concerns that are usually handled at the guidance and counselling centres, modes of providing guidance and counselling services, organisation and administration of guidance programme and challenges confronting privately owned counselling centres in Nigeria. It is concluded that Nigeria needs counselling to address its challenges, therefore, counselling should be given more attention through empowerment of private organisations that are interested in establishing counselling centres.